Implementation of Managerial Supervision and Islamic Communication at Madrasah Aliyah Negeri South Tapanuli Regency - Fahrul Sanawi; Wahyudin Nur; Amiruddin Siahaan; Selamat Pasaribu (Pena Justisia: Media Komunikasi dan Kajian Hukum, 2025)
This study aims to determine the implementation of Islamic supervision and communication at the State Islamic Senior High School (MAN) and the Insan Cendekia State Islamic Senior High School in South Tapanuli Regency, North Sumatra. The study was conducted qualitatively from January to September 2024. Informants consisted of the head of the school, the deputy head of curriculum, teachers, and students. The results of the study show: (1) Supervision of curriculum management and learning in both schools is carried out systematically, with well-organised plans and documentation, and the active role of the school's deputy head for curriculum. (2) Student supervision focuses on monitoring students' academic and social development. (3) Supervision of facilities and infrastructure is managed well, through inventory, periodic maintenance, and adequate budget support. (4) Supervise personnel, clearly divide tasks, monitor performance, and train and develop professional education personnel. (5) Implementing Islamic communication shows a positive relationship between the school and the community, as evidenced by active partnerships through joint activities such as social services and school committee meetings. Effective communication between the school and parents supports improving the quality of education. Overall, Islamic supervision and communication played an important role in enhancing mutual management and community involvement in education in both madrasahs.